Synthesis of Ca3(PO4)2 from Tuna Fish Bone Intercalated on Bentonite and Applied as Catalyst To Produce of Biodiesel From Waste Cooking Oil - Admin Icirpe (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The Ca3(PO4)2-bentonite was applied as a catalyst in synthesizing of biodiesel from waste cooking oil have beenconducted. The Ca3(PO4)2 catalyst synthesis was carried out using a simple method by calcining tuna fish bonepowder at temperatures of 600 oC, 700 oC, 800 oC, 900 oC and 1000 oC. The best results obtained are used asmaterials for the intercalation process. The intercalation process initiaed by addition of CTAB into bentonite, stirringat medium speed for 24 hours and followed by addition of Ca3(PO4)2 and stirring for 24 hours. The intercalationresults were calcined at 600 oC for 2 hours, then characterized by XRD, SEM, FTIR, and BET. The resulted catalystthen applied in transesterification reaction to produce biodiesel from the waste cooking oil. The XRD analysis resulthave shows the highest Ca3(PO4)2 obtained at 1000 oC calcination process, this conclusion is reinforced by theresults of characterization, namely the presence of a peak at 2θ: 32,05o; 33,20o; 39,95o. The intercalation processhave taken place perfectly which is indicated by the BET test showing a decrease in the bentonite surface area of 65m2/g to 39 m2/g also supported by SEM which shows the inclusion of Ca3(PO4)2 into the bentonite cavity. TheCa3(PO4)2-bentonite has been synthesized successfully catalyzes the production of biodiesel from waste cooking oilwith a yield of 40.91% with the main component that resulted is methyl stearic (24.05%).